The engine of complexity : evolution as computation - Mayfield, John E. (Columbia University Press, 2013)
The concepts of evolution and complexity theory have become part of the intellectual ether permeating the life sciences, the social and behavioral sciences, and more recently, management science and economics. In this new title, John Mayfield elegantly synthesizes core concepts from across disciplines to offer a new approach to understanding how evolution works and how complex organisms, structures, organizations, and social orders can and do arise based on information theory and computational science. This is a big picture book intended for the intellectually adventuresome. While.